Blocking the solution: Social representations of threats and (non)dialogue with alternative representations in Greek-Cypriot newspapers during peace negotiations - Avraamidou, Maria; Psaltis, Charis (My University, 2019)
This paper first identifies representations of threats in Greek-Cypriot newspapers related to the negotiations for a Cyprus settlement. Then, it identifies how alternative representations to these core representations of threats are managed through the use of a number of semantic barriers. Therefore, it problematizes the role (function) that such representations of threats play in undermining the potential for transformative dialogue in a post-conflict and divided country in need of conflict transformation. Focus is on the editorials of two newspapers during a four-month period before the collapse of the July 2017 Cyprus peace talks. Both were suspicious and polemic vis-à-vis the said negotiations but used different strategies to oppose them. Simerini convened recurrently threats such as Turkification, state dissolution and threats against Hellenism. Phileleftheros focused on the issue of security drawing red lines on various dossiers under discussion in the negotiations. The paper contributes to the theoretical debate of the relationship between social representations and identities and the role of threats and historical narratives in undermining transformative dialogue through the use of semantic barriers.
Keywords: Conflict; Cyprus; Media analysis; Propaganda; Realistic threats; Semantic barriers; Social representations; Symbolic threats